А)[latex]arcctg1-arctg \sqrt{3}-arccos(- \frac{1}{2}) [/latex]b)[latex]arcsin(- \frac{1}{2})+arctg(- \frac{1}{\sqrt{3} } -arcctg \sqrt{3} [/latex]c)[latex]arcsin(-1)- \frac{3}{2}arccos \frac{1}{2}+3arcctg(- \frac{1}{\sqrt{3} })...
А)[latex]arcctg1-arctg \sqrt{3}-arccos(- \frac{1}{2}) [/latex]
b)[latex]arcsin(- \frac{1}{2})+arctg(- \frac{1}{\sqrt{3} } -arcctg \sqrt{3} [/latex]
c)[latex]arcsin(-1)- \frac{3}{2}arccos \frac{1}{2}+3arcctg(- \frac{1}{\sqrt{3} }) [/latex]
d)[latex]-4*arcsin( \frac{\sqrt{2} }{2}+8arccos( \frac{\sqrt{2} }{2} )-15*arctg \frac{\sqrt{3} }{3} [/latex]
Ответ(ы) на вопрос:
[latex]arcctg1-arctg\sqrt3-arccos(-\frac{1}{2})=\frac{\pi}{4}-\frac{\pi}{3}-(\pi -\frac{\pi}{3})=-\frac{3\pi}{4}\\\\b)\; arcsin(-\frac{1}{2})+arctg(-\frac{1}{\sqrt3})-arcctg\sqrt3=-\frac{\pi}{6}-\frac{\pi}{6}-\frac{\pi}{6}=-\frac{3\pi}{6}=-\frac{\pi}{2}\\\\c)\; arcsin(-1)-\frac{3}{2}arccos\frac{1}{2}+3arcctg(-\frac{1}{\sqrt3})=-\frac{\pi}{2}-\frac{3}{2}\cdot \frac{\pi}{3}+3(\pi -\frac{\pi}{3})=\\\\=-\frac{\pi}{2}-\frac{\pi}{2}+2\pi =-\pi +2\pi =\pi [/latex]
[latex]d)\; -4arcsin\frac{\sqrt2}{2}+8arccos\frac{\sqrt2}{2}-15arctg\frac{\sqrt3}{3}=-4\cdot \frac{\pi}{4}+8\cdot \frac{\pi}{4}-15\cdot \frac{\pi}{6}=\\\\=-\pi +2\pi -\frac{15}{6}\pi =-\frac{9}{6}\pi =-\frac{3}{2}\pi [/latex]
Не нашли ответ?
Похожие вопросы